Work Readiness of UKI Toraja Faculty of Economics Students: Integration of Academic Ability and Talent Management In the Perspective of Human Capital Theory - Pagiu, Chrismesi; Pundissing, Rati; Maharani, Elsa (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze the integration of academic ability and talent management on the work readiness of students of the Faculty of Economics UKI Toraja from the perspective of human capital theory. Data collection techniques by filling out questionnaires by students of the Faculty of Economics UKI Toraja who have participated in the Work World Practice, Internship and Certified Independent Study (MSIB), Entrepreneurship Internship activities using SEM-Smart PLS. The results of the study showed that Academic Ability influenced Work Readiness with a coefficient of 0.494, a t value of 6.286, and a p-value of 0.000, while Talent Management influenced Work Readiness with a coefficient of 0.473, a t value of 5.739, and a p-value of 0.000. Academic Ability and Talent Management simultaneously influenced Work Readiness significantly with an F value of 328.973 and a p-value of 0.000. The academic ability variable has the greatest influence compared to talent management with a coefficient value of 0.494.